Conflicting rights: How the prohibition of human trafficking and sexual exploitation infringes the right to health of female sex workers in Phnom Penh, Cambodia - Maher, Lisa (Health Hum Rights, 2015)
While repressive laws and policies in relation to sex work have the potential to undermine HIV prevention efforts, empirical research on their interface has been lacking. In 2008, Cambodia introduced anti-trafficking legislation ostensibly designed to suppress human trafficking and sexual exploitation. Based on empirical research with female sex workers, this article examines the impact of the new law on vulnerability to HIV and other adverse health outcomes. Following the introduction of the law, sex workers reported being displaced to streets and guesthouses, impacting their ability to negotiate safe sex and increasing exposure to violence. Disruption of peer networks and associated mobility also reduced access to outreach, condoms and health care. Our results are consistent with a growing body of research which associates the violation of sex workers’ human rights with adverse public health outcomes. Despite the successes of the last decade, Cambodia’s AIDS epidemic remains volatile and the current legal environment has the potential to undermine prevention efforts by promoting stigma and discrimination, impeding prevention uptake and coverage, and increasing infections. Legal and policy responses which seek to protect the rights of the sexually exploited should not infringe the right to health of sex workers.